2021
DOI: 10.1002/aoc.6238
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the catalytic performance of manganese (III)‐porphyrin complex MnTSPP for facile one‐pot green synthesis of 1,4‐dihydropyridine derivatives under mild conditions

Abstract: In this study, the metal complex (5,10,15,20‐tetrakis‐(4‐sulfonatophenyl)‐porphyrin manganese (III) chloride; denoted as MnTSPP) represents a promising efficient and reusable heterogeneous solid catalyst for facile and highly efficient one‐pot synthesis of 1,4 dihydropyridine derivatives via three‐component condensation reaction of aromatic aldehyde, ethyl acetoacetate, and ammonium acetate under green and mild reaction conditions. The simple operation, short reaction time (15 min), and the high efficiency (99… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…The most important method for the synthesis of 1,4-dihydropyridine was the application of dimedone, acetoacetate, aldehyde derivatives, and ammonium acetate using various catalysts ( Calvino-Casilda and Martín-Aranda, 2020 ; Ali El-Remaily et al, 2021 ; Maleki et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most important method for the synthesis of 1,4-dihydropyridine was the application of dimedone, acetoacetate, aldehyde derivatives, and ammonium acetate using various catalysts ( Calvino-Casilda and Martín-Aranda, 2020 ; Ali El-Remaily et al, 2021 ; Maleki et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, high yields of products were found for heteroaryl aldehydes (Table 2, entries 17–20). 28,54–60…”
Section: Resultsmentioning
confidence: 99%
“…A possible mechanism for the catalytic reaction was arrived based on earlier studies (Figure 10). 72 To test the catalytic nature of this reaction, we have carried out a hot-filtration study. The hot-filtration study, employing compound I, indicated that the reaction did not proceed in the absence of the catalyst�though a small increase in the product was observed over the course of the reaction time of 60 min (Figure S25).…”
Section: Structure Of [{Cu 6 (Mna )6 }{Mn(bpy)h 2 O} 2 {Mn(h 2 O) 4 }...mentioning
confidence: 99%